High‐grade traumatic torso visceral injury with hemodynamic instability: effectiveness of transarterial embolization using n‐butyl cyanoacrylate. Issue 2 (6th March 2017) - Tsurukiri, Junya; Ohta, Shoichi; Hoshiai, Akira; Sano, Hidefumi; Okumura, Eitaro; Tsubouchi, Nobuhiko; Konishi, Hiroyuki; Yukioka, Tetsuo
Abstract : Trauma patients with uncontrolled hemorrhage encountering coagulopathy are often associated with poor outcome. Recently, the concept of damage control interventional radiology, which focuses on "speedy stoppage of bleeding" by interventional radiology among trauma patients with hemodynamic instability and acute traumatic coagulopathy, was proposed as an alternative to damage control surgery. N‐butyl cyanoacrylate (NBCA) has been used as a liquid embolic agent in various non‐traumatic situations, where it has been shown to have a high technical success rate and low recurrent bleeding rate, especially in patients with coagulopathy. In this case, we treated a young patient with hemodynamic instability caused by a high‐grade hepatic injury, who underwent arterial embolization (AE) using NBCA assisted with resuscitative endovascular balloon occlusion of the aorta and achieved successful hemostasis. A review of published works using PUBMED was carried out, and 10 published reports involving 23 trauma patients who underwent AE using NBCA were identified. Among them, only four reports involving five trauma patients with torso visceral injuries were identified. Three of five patients who were hemodynamically unstable underwent AE using NBCA, resulting in the stabilization of hemodynamics. We concluded that AE with resuscitative endovascular balloon occlusion of the aorta as a damage control interventional radiology procedure might be acceptable for the hemodynamically unstable hepatic injury, and NBCA could be one of the effective hemostatic agents for this purpose, in cases of trauma‐induced coagulopathy. Abstract : Arterial embolization with resuscitative endovascular balloon occlusion of the aorta as a damage control interventional radiology procedure might be acceptable for the hemodynamically unstable hepatic injury. N‐butyl cyanoacrylate could be one of the effective hemostatic agents for this purpose, in cases of trauma‐induced coagulopathy.